The impact of cross-listing in the United States on the precision of public and private information - Herrmann, Don; Kang, Tony; Yoo, Yong Keun (Journal of International Business Studies, 2015)
Our study explores the source of improvement in the information environment from cross-listing shares on US stock exchanges. Are the improvements from cross-listing in the United States achieved more through public or private information channels? While we find evidence that US cross-listing is significantly associated with improvements in both public and private information precision, the association is stronger between cross-listing and improvements in private information precision. This suggests that the improvement in the information environment for cross-listed firms is largely due to analysts expending more effort on firm-specific information discovery as opposed to broader improvements in overall public disclosure. This research should influence international business scholars that improvements in the information environment do not occur solely through public information channels. They also occur through investors’ private information search activities.